Fine-scale columnar and surface nox concentrations over South Korea: Comparison of surface monitors, tropomi, cmaq and capss inventory - Kim, Hyun Cheol; Kim, Soontae; Lee, Sang Hyun; Kim, Byeong Uk; Lee, Pius (Atmosphere, 2020)
Fine-scale nitrogen oxide (NOx) concentrations over South Korea are examined using surface observations, satellite data and high-resolution model simulations based on the latest emission inventory. While accurate information on NOx emissions in South Korea is crucial to understanding regional air quality in the region, consensus on the validation of NOx emissions is lacking. We investigate the spatial and temporal variation in fine-scale NOx emission sources over South Korea. Surface observations and newly available fine-scale satellite data (TROPOspheric Monitoring Instrument; TROPOMI; 3.5 x 7 km2) are compared with the community multiscale air quality (CMAQ) model based on the clean air policy support system (CAPSS) 2016 emission inventory. The results show that the TROPOMI NO2 column densities agree well with the CMAQ simulations based on CAPSS emissions (e.g., R = 0.96 for June 2018). The surface observations, satellite data and model are consistent in terms of their spatial distribution, the overestimation over the Seoul Metropolitan Area and major point sources; however, the model tends to underestimate the surface concentrations during the cold season.
Keywords: Community multi-scale air qualities; Emission inventories; High-resolution models; Monitoring instruments; Regional air quality; Seoul metropolitan area; Spatial and temporal variation; Surface concentration; Air quality; CMAQ; Emission inventory; NOx; TROPOMI